ALS-specific cognitive and behavior changes associated with advancing disease stage in ALS. (9th October 2018) - Crockford, Christopher; Newton, Judith; Lonergan, Katie; Chiwera, Theresa; Booth, Tom; Chandran, Siddharthan; Colville, Shuna; Heverin, Mark; Mays, Iain; Pal, Suvankar; Pender, Niall; Pinto-Grau, Marta; et al.
Abstract : Objective: To elucidate the relationship between disease stage in amyotrophic lateral sclerosis (ALS), as measured with the King's Clinical Staging System, and cognitive and behavioral change, measured with the Edinburgh Cognitive and Behavioural ALS Screen (ECAS). Methods: A large multicenter observational cohort of 161 cross-sectional patients with ALS and 80 healthy matched controls were recruited across 3 research sites (Dublin, Edinburgh, and London). Participants were administered the ECAS and categorized into independent groups based on their King's clinical disease stage at time of testing. Results: Significant differences were observed between patients and controls on all subtests of the ECAS except for visuospatial functioning. A significant cross-sectional effect was observed across disease stages for ALS-specific functions (executive, language, letter fluency) and ECAS total score but not for ALS-nonspecific functions (memory, visuospatial). Rates of ALS-specific impairment and behavioral change were also related to disease stage. The relationship between cognitive function and disease stage may be due to letter fluency impairment, whereas higher rates of all behavioral domains were seen in later King's stage. The presence of bulbar signs, but not site of onset, was significantly related to ALS-specific, ECAS total, and behavioral scores. Conclusion: ALS-specific cognitive deficits and behavioral impairment are more frequent with more severe disease stage. By end-stage disease, only a small percentage of patients are free of neuropsychological impairment. The presence of bulbar symptoms exaggerates the differences observed between disease stages. These findings suggest that cognitive and behavioral change should be incorporated into ALS diagnostic criteria and should be included in future staging systems.